Peran Orang Tua dalam Pengembangan Bahasa Anak Usia Dini - Pradita, Erika Lia; Kumala Dewi, Anisa; Nasywa Tsuraya, Nisrinda; Fauziah, Muhardila (Indo-MathEdu Intellectuals Journal, 2024)
Parents have a role in assisting their children in completing developmental tasks, including the development of language skills. Every action and spoken word of parents in the family and social environment will influence the child's language development. This research aims to describe the importance of the role of parents in the early language development of children in Kulon Progo. The method used in this research is descriptive qualitative research with analysis using the model by Miles and Huberman. The instrument used in this research is interviews. The subjects of this study are parents with children aged 0-6 years, and 2 individuals were determined as subjects. The results of this study indicate that the role of parents significantly influences the language development of children. The motivation of parents in developing their children's language abilities can affect and accelerate language development. Guidance or teaching provided by parents in a directed manner will align with the child's age, making language development easier and more controlled as the child grows older. The child's language proficiency is enhanced when parents consistently provide encouragement using something that aids the child's language development. Additionally, the environmental conditions also play a crucial role in the language development of children. A conducive environment fosters and guides children, making it easier for them to develop good and correct language skills.